Perception or response bias?: evaluating competing hypotheses through automation of action-control - Tenhundfeld, Nathan L., author; Witt, Jessica, advisor; Clegg, Benjamin, committee member; Gibbons, Alyssa, committee member; Smith, Charles A. P., committee member; Wickens, Christopher, committee member (Colorado State University. Libraries, 2017)
The claim of action-specific researchers is that one's ability to act affects his or her perception of the environment. When using a reach extending tool, such as a stick, objects appear closer than they do without using that stick. However, whether these effects are perception or simply a response bias has been hotly contested. In this dissertation, four experiments were run using the Pong task to be able to differentiate between a response bias and evidence for a perceptual account. Results indicate that not only were results not in line with a response bias account, but they were what the action-specific account of perception would predict. Results are discussed in context of what this means for theories of visual perception. Results are then discussed in relation to the motor simulation hypothesis to evaluate its validity as an explanation for action-specific effects. Finally, given the nature of the experimental design, a framework for a Theory of Automation Embodiment is developed.
Keywords: automation embodiment; perception; embodied perception; automation